Pengujian Fungsionalitas dan Kualitas Website Wisata Kotawaringin Timur Menggunakan Metode Black Box dan Standar ISO - Minarni Minarni; Sigit Sigit (LPPM STIKI MALANG, 2023)
This study aims to test the functionality and quality of the East Kotawaringin tourism website recommendation application using the black box method and ISO standards. Testing and implementation of this tourism website was also carried out using the Likert Scale as a survey instrument to determine the level of satisfaction of respondents. The respondents to this study included the Kotim Kominfo Service, the Kotim Culture and Tourism Office, university students, and the general public of East Kotawaringin. The East Kotawaringin Office of Communication and Information (Kominfo) is responsible for managing the hosting and domain of this tourism website, while the East Kotawaringin Culture and Tourism Office is the user and manager of the website. Therefore, this website really needs to be tested for functionality and quality for optimal use of the website as a provider of information for the public and tourists. Factors tested include functionality, usability, efficiency and portability. The results of testing this website show that travel websites have good results in terms of functionality, usability, efficiency and portability. However, there are still deficiencies in terms of security or security in the functional section.